Visualized Creative Graphics Expression in the Dynamic Research of the Intelligence Media Era - Xue, Siqi (Transactions on Social Science, Education and Humanities Research, 2023)
In the era of intellectual media, visualized creative graphics expression became one of the important ways of information dissemination. This thesis aims to study the dynamic trend of visualized creative graphics in the era of intellectual media, explore its applications, problems, and future prospects. The problems of technological innovation, multimedia integration, and user interaction in this field revealed the widespread application of creative dynamic graphics in the fields of digital media art, art design, social media and advertising. At the same time, in -depth analysis of the challenges of technology and content, and pointed out the possible development trends in the future, including the continuous progress of technology, the personalization of content, and the increase in user participation. This study has important theoretical and practical value for understanding the dynamics and importance of visual creative graphics in the era of wisdom media, as well as corresponding strategies and solutions.